Analisis Pemeliharaan Pada Mesin Injection Molding Menggunakan Metode Total Productive Maintenance (TPM) Dengan Pendekatan Overall Equipment Effectiveness (OEE) - Ardhi Prasetyo Buono; Ade Momon Subagyo (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. XYZ, which is a company that operates in the plastic injection industry, has a machine that operates for a long time and causes a decrease in the performance of the machine. The Body Koito K11A machine is one of the machines that has a long operational time in a day so maintenance activities are needed to avoid damage to the machine. Total Productive Maintenance is a method used to identify problems in machine maintenance using Overall Equipment Effectiveness. The OEE calculation considers 3 aspects, namely availability, performance and quality. With the OEE, the analysis of maintenance on the machine PT. XYZ can be assessed the root of the problem. The purpose of this study was to determine how much the OEE value on the PT. XYZ.